PENGARUH HARGA DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN ASURANSI KENDARAAN BERMOTOR PT. ASURANSI JASINDO (PERSERO) CABANG PALU - Latoki, Labandingi; Chalil, H Chalil; Ponirin, Ponirin (Katalogis, 2018)
The study uncovers the influence of price and service quality on the satisfaction of motor vehicle insurance's customers in PT. Asuransi Jasindo (Persero) of Palu Branch. The aim to achieved is to determine and analyze the positive and significant influence of price and service quality on consumer's satisfaction of vehicle insurance in PT. Asuransi Jasindo Palu. Type of research is verificative with questionnaires as its instrument that distributed to 184 respondents. The results indicate that price has positive and significant influence on customers' satisfaction. Parameter estimation in table 4.28 between variables of price and customer satisfaction is significant because p value is lower than the level of significance of 5% or 0,05 that is equal to 0,004. The estimated value between variables of price and customer satisfaction is 0,522 which means if the price increased, then the customer satisfaction will also increase. Service quality has a positive and significant influence on customer satisfaction. Parameter estimation in table 4.28 between variables of service quality and customer satisfaction is significant because p value is tower than the level of significance of 5% or 0,05 that is equal to 0,036. The value of estimation between variables of service quality and customer satisfaction equals to 0,396, which means that if service quality increased by 1, customer satisfaction will also increase.